Penggambaran Hedgehog Dilemma dalam Anime Neon Genesis Evangelion Karya Hideaki Anno - I Dewa Ketut, Aruna Jagathita; Ni Luh Putu Ari Sulatri; I Gede Oeinada (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2026)
This study aims to describe the characteristics and contributing factors of the hedgehog dilemma in the anime Neon Genesis Evangelion.. The theories used in this research are the psychological approach to literature by Wiyatmi and the Fundamental Interpersonal Relations Orientation-Behavior (FIRO-B) theory by Schutz. This study employs the observational method and note-taking technique for data collection. The primary data source is the Neon Genesis Evangelion anime series. The collected data is analyzed using a descriptive analytical approach by Ratna (2004) and presented using the informal method also by Ratna (2004). The findings reveal the presence of the hedgehog dilemma in several behaviors described in the FIRO-B theory, including undersocial, autocratic, and overpersonal behaviors. The factors contributing to the hedgehog dilemma as depicted in the anime include: (1) unmet needs for selfacceptance, (2) unmet needs for control, and (3) past trauma. This study found  that  the hedgehog dilemma can be a limitation of interpersonal relationships and tends to occur in individuals whose interpersonal needs are not met.